Transformasi Bank Sampah Kuntum Mekar Tonjong sebagai Destinasi Eduwisata melalui Peningkatan Kapasitas SDM dan Digitalisasi Promosi - Yulita Suryantari; Elisabeth Ria Viana Praningtyas; Rezki Orientani; Ramdhan Kurniawan; Refaldi Maulana (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to transform Kuntum Mekar Waste Bank in Bogor into an independent and sustainable educational tourism destination through human resource capacity building and promotional digitalization. The program involved 20 partners who were the managers of Kuntum Mekar Waste Bank. Implementation was carried out using participatory education, training, and mentoring methods. Program evaluation was conducted through pre-test and post-test assessments, observation sheets, and interviews, which were analyzed descriptively. The results showed an improvement in partners’ understanding and skills in managing environmentally based educational tourism. In addition, the partners’ ability to utilize digital media as a promotional tool also increased, accompanied by the development of recycled products with economic value. The educational tourism website developed through the program proved to function effectively as a medium for information dissemination and marketing. This program also generated several outputs, namely an educational tourism website, educational posters, media publications, documentary videos, and Intellectual Property Rights (IPR).